A Study in the historical realm of Mouhmed Cherif Sahli (1906-1989) - boudjit, amal; settar, Othmani (The Algerian Historical Journal, 2026)
Our article focused on an aspect of the life of Mohamed Chérif Sahli, who was a student, then a teacher, a journalist, an activist, and a freedom fighter for the liberation of Algeria from the grip of French colonialism. Despite studying philosophy, he chose to delve into the field of history. He started as a journalist and later becoming a historian. He wrote about important national figures such as Jugurtha and Emir Abdelkader after World War II. However, his book "Decolonizing History," was published after Algeria gained independence in 1965.It gained significant popularity among intellectual circles. Sahli was among the first to recognize the importance of history in the national movement and its profound contribution to building an independent Algeria.